AN ANALYSIS STUDENTS DIFFICULTIES IN USING THE SIMPLE PRESENT TENSE IN REPORT TEXT BY CLASS XI IPA 1 SMAN 2 KUTACANE IN ACADEMIC YEAR 2023/2024 - Anggi Aprila NST; Wahyu Fatahillah; Edi Syahputra (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
Simple present tense is the part of the tense that must mastered by students in learning English if students have not fully understood the material of simple present tense then it can result in the achievement of student learning outcomes, see the formulation of the problem in this study, namely: what kind of difficulty students have in using simple present tense. This study uses a qualitative descriptive method that aims to determine the difficulties of students in using simple present tense by grade XI IPA 1 students. Data collection in this study was a questionnaire consisting of 20 students as a source of data in research. The result showed that there were 3 aspects of students difficulty in using simple present tense, including grammar, use of simple present and adverb of time. based on the research data obtained there are 3 students who choose the least correct answer (on grammar) then on (use of simple present) there are 1 students who choose the least correct answer and for (adverb of time) there were 8 students who answered the statement although not all were answered correctly. This shows that for all three aspects of this study, adverb of time is one of the levels of difficulty faced by students in learning tenses. Meanwhile, for the overall percentage of students in understanding and using simple present there are 18.06% (in grammar), then 37.3% (in use simple present) and the last 45% (in adverb of time).